Monitoring the Breath-Hold Training Load during an Ecological Session: A Pilot Study - Allinger, Jérémie; Bouyeure, Antoine; Noulhiane, Marion; Lemaitre, Frederic (International Journal of Sports Medicine, 2024)
This study aimed to create a training load index to measure physiological stress during breath-hold (BH) training and examine its relationship with memory performance. Eighteen well-trained BH divers (Age: 35.8±6.6 years, BH training practice: 5.3±4.5 years) participated in this study. During a standard 1.5-hour BH training in the pool, perceived exertion, heart rate, distance, and duration were measured. The training load index was modelled on the basis of a TRIMP (TRaining IMPulse) with four different equations and was used to measure the stress induced by this BH training. A reference value, based on the ratio between the average heart rate during all BHs and the lowest heart rate during BH training, was used for comparing training load index. Memory assessment was conducted both before and after this training. Of the four equations proposed, equation no. 4, named aTRIMP for “apnoea,” showed the strongest correlation with our reference value (r=0.652, p<0.01). No difference was found between any of the memory tests before and after the BH training. The aTRIMP was a new representative index for monitoring habitual training of well-trained BH divers. Furthermore, this training had no negative impact on memory performance.
Keywords: apnea performance; freediving; cognition